Simulative investigation on head injuries of electric self-balancing scooter riders subject to ground impact - Xu, Jun; Shang, Shi; Qi, Hongsheng; Yu, Guizhen; Wang, Yunpeng; Chen, Peng (Accident analysis and prevention, 2016)
•The kinematics of an electric self-balancing scooter (ESS) involved accidents are investigated.•A combined method of kinetic analysis and finite element analysis is suggested.•Parametric studies are conducted to study the governing effects on the head injury.•ESS riders may suffer severe brain injuries from secondary contact to the ground. The safety performance of an electric self-balancing scooter (ESS) has recently become a main concern in preventing its further wide application as a major candidate for green transportation. Scooter riders may suffer severe brain injuries in possible vehicle crash accidents not only from contact with a windshield or bonnet but also from secondary contact with the ground. In this paper, virtual vehicle–ESS crash scenarios combined with finite element (FE) car models and multi-body scooter/human models are set up. Post-impact kinematic gestures of scooter riders under various contact conditions, such as different vehicle impact speeds, ESS moving speeds, impact angles or positions, and different human sizes, are classified and analyzed. Furthermore, head–ground impact processes are reconstructed using validated FE head models, and important parameters of contusion and laceration (e.g., coup or contrecoup pressures and Von Mises stress and the maximum shear stress) are extracted and analyzed to assess the severity of regional contusion from head–ground contact. Results show that the brain injury risk increases with vehicle speeds and ESS moving speeds and may provide fundamental knowledge to popularize the use of a helmet and the vehicle-fitted safety systems, and lay a strong foundation for the reconstruction of ESS-involved accidents. There is scope to improve safety for the use of ESS in public roads according to the analysis and conclusions.